Research and Policy Issues in High-Skilled International Migration: A Perspective with Data from the United States - Mark C. Regets (Institute for the Study of Labor (IZA), 2001)
Highly-skilled migrants are becoming a more important part of the world economy and of policy debates in a diverse set of countries. The proliferation of skills around the world, increases in world trade, the growth of R&D, and the general increase in the labor market demand for diverse sets of skills, have all contributed to the emergence of high-skilled migration as a major issue. High-skilled migration is often discussed in narrow terms of ?brain drain/brain gain?, when both the pattern of migration and its effects appear to be much more complex. However, our understanding of the effects of high skilled migration is much less than for international migration in general, and is based upon much less research and data. This paper reviews the possible effects of high skilled international migration, and the major research and policy questions that need answering.
Keywords: J44; J16; J21; J24; F02; F22; 330; Migration; skilled labor; doctorate; brain drain; Brain Drain; Internationale Arbeitsmobilität; Hochqualifizierte Arbeitskräfte; Kosten-Nutzen-Analyse; USA; Welt